Immediate effects of acupuncture on strength performance: a randomized, controlled crossover trial - Hübscher, M.; Vogt, L.; Ziebart, T.; Banzer, W. (European Journal of Applied Physiology, 2010)
The present study investigated the immediate efficacy of acupuncture compared to sham acupuncture and placebo laser acupuncture on strength performance. A total of 33 recreational athletes (25.2 ± 2.8 years; 13 women) were randomized to receive acupuncture, sham acupuncture (needling at non-acupuncture points) and placebo laser acupuncture (deactivated laser device) in a double-blind crossover fashion with 1 week between trials. Assessment included bipedal drop jumps for maximum rebound height and quadriceps maximum isometric voluntary force (MIVF). Furthermore, surface electromyography (EMG) was used to measure the EMG activity of the rectus femoris muscle during a 30-s sustained MIVF of the knee extensors. Mean power frequency (MPF) analysis was applied to characterize muscular endurance. Measurements were performed at baseline and immediately after treatment by a blinded investigator. Repeated measures ANOVA and post hoc paired-sample t test with Bonferroni-Holm correction were used for statistical analysis. The difference in the mean change in MIVF from baseline between acupuncture (46.6 N) and sham laser acupuncture (19.6 N) was statistically significant (p < 0.05), but no significant difference was found between acupuncture (46.6 N) and sham acupuncture (28.8 N). ANOVA did not show statistically significant treatment effects for drop jump height or MPF. The present study shows that a single acupuncture treatment was efficacious for improving isometric quadriceps strength in recreational athletes. These results might have implications not only for athletic performance enhancement, but also for rehabilitation programs aimed at restoring neuromuscular function.